The emergence of the modern neo-pentecostal prince from the lag of political parties as a form of collective organization - Carvalho, Renan Augusto (Laboratório Editorial Faculdade de Ciências e Letras, 2021)
The 20th century’s successful experiences of combining capitalism and democracy allowed Gramsci’s diagnosis to be confirmed from the rereading of Machiavelli: political parties would be capable of creating a particular cultural and societal organization. However, in the Brazilian case, such organizations appear with greater vigor in public life after democratic opening, situated in a global environment of the diminished performance of these associations. Beholding the loss of this space of action, the present work addresses the action of neo-pentecostalism in the reconfiguration of the modern prince, achieving a certain collective will and re-updating the institutional political scenario.